Millennium BCP- The almond hill credit extension proposal - Preto, Antonio Jose Raposo Bordalo Ramos (2015)
This Work Project is a case study on the credit lending process and loan pricing policy of Millennium bcp, one of the main Portuguese banks. The goal of the case study is to provide an opportunity to understand the above mentioned process and policy in a major bank and to explore the issues and interests at play when a relevant credit decision must be taken. I would like to thank Dr. José Miguel Pessanha without whom this project would not have been possible.